A New Institutional Economic Perspective on Alternative Governance Mechanisms at the Local Government Level. (January 2023) - Wallis, Joe; Rizvi, Syed
The 'new institutional economics' (NIE) can go a long way towards comprehending the emerging complexities of local government. As local bodies seek to forge collaborative partnerships with other organisations, they have to decide whether to solve horizontal co-ordination problems through market, hierarchy or network mechanisms. NIE can show that where other governance mechanisms are incomplete or subject to high transaction costs, trust and co-operation can informally develop through the process by which network interactions become embedded within each other. We show how this approach can be revised to take into account the expressive dimension of behaviour in hope-based networks whose members are bound together not so much by structures of resource dependence as by the hope and trust they place in the advancement of common goals. JEL: L38